Reconfigurable FIR Filter in FPGA - Dzukleski, Igor; Ortega-Sanchez, Cesar (Murdoch University, 2006)
Finite Impulse Response (FIR) filters are widely used in Digital Signal Processing (DSP) systems. The throughput of real-time, FIR filters is limited by the processing capability of its implementation. Software implementations are very flexible but the inherent sequential execution of programs makes them slow. The fastest FIR filters are those implemented in dedicated hardware, but these systems are usually fixed and modifications to the filter are not possible. This paper presents the design and implementation of a Field-Programmable Gate-Array (FPGA)-based, FIR filter. By exploiting the field-programmability of FPGAs it is possible to create different filters with fixed functionality, or even create adaptive filters whose parameters are adjusted in real-time by some intelligent algorithm.